2023
DOI: 10.1182/blood.2023022136
|View full text |Cite
|
Sign up to set email alerts
|

Anti-PF4 immunothrombosis without proximate heparin or adenovirus vector vaccine exposure

Linda Schönborn,
Olga Esteban,
Jan Wesche
et al.

Abstract: Platelet-activating anti-platelet factor 4 (PF4)/heparin antibodies and anti-PF4 antibodies cause heparin-induced thrombocytopenia (HIT) and vaccine-induced immune thrombocytopenia and thrombosis (VITT), respectively. Diagnostic and treatment considerations differ somewhat between HIT and VITT. We identified patients with thrombocytopenia and thrombosis without proximate heparin exposure or adenovirus-based vaccination who tested strongly positive by PF4/polyanion EIA and negative/weakly-positive by heparin-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 35 publications
2
0
0
Order By: Relevance
“…A similar finding was also reported by Schönborn et al [72], who identified nine patients with VITT-like clinical and humoral profiles from a retrospective analysis of repository serum samples dated before 2020 [72]. These individuals experienced acute thrombocytopenia, significantly elevated D-dimer, and severe thrombotic events, including arterial strokes and CVST, without recent exposure to heparin or adenoviral vector-based vaccines [72]. Thus, the association of pro-thrombotic anti-PF4 antibodies with disorders showing clinical and/or pathological similarities to VITT may be indicative of an unknown trigger for pathogenic antibody production beyond our current scope of understanding.…”
Section: Vitt-mimicking Anti-pf4 Antibodies In Hit and Other Disorderssupporting
confidence: 92%
See 1 more Smart Citation
“…A similar finding was also reported by Schönborn et al [72], who identified nine patients with VITT-like clinical and humoral profiles from a retrospective analysis of repository serum samples dated before 2020 [72]. These individuals experienced acute thrombocytopenia, significantly elevated D-dimer, and severe thrombotic events, including arterial strokes and CVST, without recent exposure to heparin or adenoviral vector-based vaccines [72]. Thus, the association of pro-thrombotic anti-PF4 antibodies with disorders showing clinical and/or pathological similarities to VITT may be indicative of an unknown trigger for pathogenic antibody production beyond our current scope of understanding.…”
Section: Vitt-mimicking Anti-pf4 Antibodies In Hit and Other Disorderssupporting
confidence: 92%
“…Serum samples from these two patients were positive for anti-PF4 antibodies in both solid and fluid phases assays, and in PF4-enhanced platelet-activation assays, and demonstrated binding to the heparin-binding region on PF4 [64]. A similar finding was also reported by Schönborn et al [72], who identified nine patients with VITT-like clinical and humoral profiles from a retrospective analysis of repository serum samples dated before 2020 [72]. These individuals experienced acute thrombocytopenia, significantly elevated D-dimer, and severe thrombotic events, including arterial strokes and CVST, without recent exposure to heparin or adenoviral vector-based vaccines [72].…”
Section: Vitt-mimicking Anti-pf4 Antibodies In Hit and Other Disorderssupporting
confidence: 86%
“…A promising new approach is the recent development of a rapid chemiluminescence immunoassay (CLIA) that detects anti-PF4 (not anti-PF4/heparin) antibodies [188]; such an assay could be complementary to the existing, commercially-available, PF4/heparin-CLIA [189,190]. Approximately 30% of HIT sera yielded a positive result in the novel PF4-CLIA-presumably reflecting detection of aHIT antibodies-in addition to the expected positive result in the standard PF4/heparin-CLIA.…”
Section: Immunoassays For Ahit Antibodiesmentioning
confidence: 99%
“…It was originally reported that the binding of the adenoviral particle to PF4 could play a role in the development of VITT [21], but recent studies showed no binding between PF4 and Ad26.COV.2.S [22,23]. There is also conflicting literature associating human adenovirus infections with a prothrombotic disorder resembling VITT [24,25]. However, the high prevalence of natural human adenovirus infections without a high frequency of associated prothrombotic disorders, and the fact that TTS-like disease has also been described in patients with COVID-19 [26,27], suggests a multifactorial mechanism for VITT.…”
Section: Introductionmentioning
confidence: 99%